MicroRNA-1224-5p Inhibits Metastasis and Epithelial-Mesenchymal Transition in Colorectal Cancer by Targeting SP1-Mediated NF-κB Signaling Pathways - Li, Jie; Peng, Wen; Yang, Peng; Chen, Ranran; Gu, Qiou; Qian, Wenwei; Ji, Dongjian; Wang, Qingyuan; Zhang, Zhiyuan; Tang, Junwei; Sun, Yueming (Frontiers in Oncology, 2020)
MicroRNAs (miRNAs) are small non-coding RNAs that play pivotal roles in cancer initiation and progression. However, the roles and molecular mechanisms of miRNAs in colorectal cancer (CRC) progression remain unclear. Here, we show that downregulation of miR-1224-5p in CRC is negatively correlated with SP1 expression and metastasis in patients and xenografted mouse models. Gain- and loss-of-function assays reveal that miR-1224-5p suppresses the migration, invasion, and epithelial–mesenchymal transition (EMT) of CRC cells in vitro and in vivo by directly targeting SP1. Moreover, SP1 promotes the phosphorylation of p65, which results in EMT progress in CRC cells. Clinical analysis reveals that miR-1224-5p and SP1 expression are remarkably associated with advanced clinical features and unfavourable prognosis of patients with CRC. Further study confirms that hypoxia accounts for the depletion of miR-1224-5p in CRC. The enhancement of hypoxia during epithelial–mesenchymal transition and metastasis of CRC cells is abolished by miR-1224-5p. Our findings provide the first evidence that miR-1224-5p is a potential therapeutic target and prognostic biomarker for patients with CRC.